2019
DOI: 10.17221/481/2019-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ridge and furrow film mulching on soil environment and yield under potato continuous cropping system

Abstract: The effect of ridge and furrow film mulching (RFFM) on soil microbial communities, physicochemical property, enzymatic activity, and tuber yield were studied under the potato (Solanum tuberosum L.) continuous cropping fields managed for one (CY-1), two (CY-2) and four years (CY-4). Experimental treatments included a conventional flat plot without film mulching (FP) and five RFFM treatments: (i) a flat plot with film mulching (T1); (ii) on-ridge planting with full film mulching (T2); (iii) on-furrow planting wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…These results are consistent with those of previous studies [2,19] and indicate that reasonable plastic film mulching can improve soil nutrient contents. As we all know, plastic mulching increases soil moisture and temperature, further changing the chemical properties of soil [2,9]. During the growing season, soil pH and available P content in different treatments first increased and then decreased.…”
Section: Effects Of Film Mulching On Soil Chemical Propertiesmentioning
confidence: 98%
See 1 more Smart Citation
“…These results are consistent with those of previous studies [2,19] and indicate that reasonable plastic film mulching can improve soil nutrient contents. As we all know, plastic mulching increases soil moisture and temperature, further changing the chemical properties of soil [2,9]. During the growing season, soil pH and available P content in different treatments first increased and then decreased.…”
Section: Effects Of Film Mulching On Soil Chemical Propertiesmentioning
confidence: 98%
“…Tuber yield is closely related to soil quality, which is determined by a variety of factors including soil physical and chemical properties, enzyme activity, and microbial abundance [7][8][9]. However, with the single farming method, such as continuous planting, soil structure is destroyed, physical and chemical properties deteriorate, and storage capacity becomes poor, which in turn affects plant growth and development, leading to crop yield reduction [9][10][11][12]. As a result, new agricultural practices are urgently needed to address the worsening of soil quality and yield reduction.…”
Section: Introductionmentioning
confidence: 99%
“…It is currently the main potato production region in China. In the region, most arable lands are rainfed owing to the lack of surface water and irrigation facilities, and thus, water shortage is the major bottleneck limiting potato production (Fan et al., 2019). Low temperatures and spring droughts often occur in North China (Beijing, Tianjin, Hebei, Shanxi, Inner Mongolia), which may postpone the sowing date and delay seedling establishment, as well as hinder potato growth, tuber bulking, and tuber formation (Wang et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Film mulching directly and indirectly exerts positive impacts on the physical and chemical properties of soil and increases potato yields both quantitatively and qualitatively. In the Loess Plateau region, ridge‐furrow film mulching improves the soil environment by increasing microbial communities, soil electrical conductivity, enzymatic activities, soil heat flux, and daily integral net radiation, as well as by decreasing soil pH (Fan et al., 2019; Zhang et al., 2017b). Under the semi‐arid conditions of Indian Punjab, black polyethylene mulch produces notably higher potato yield compared to non‐mulched conditions (Sekhon et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The ridge-and-furrow planting pattern with plastic film mulching to collect rainwater has been widely applied to save water and improve the yield of many staple crops, such as wheat and maize, and has achieved good results 36 , 37 . Fan et al 38 reported that ridge-and-furrow film mulching (RFFM) enhanced microbial communities, soil electrical conductivity, and soil environment, and increased potato yields by 46.4–97.3% when compared with conventional flat plot (FP) without film mulching. Fan et al 39 found that a film fully-mulched ridge–furrow (FMRF) with a water harvesting system infused 65.7–82.7% of rainwater into the soil, doubling the soil moisture around the plant roots and enhancing the average corn yield by 14.5–22.7% when compared with conventional flat planting with mulching one-half area of soil surface (FMCF).…”
Section: Introductionmentioning
confidence: 99%